Corosolic acid ameliorates vascular remodeling in pulmonary arterial hypertension via the downregulation of STAT3 signaling - Akiko Kawade; Aya Yamamura; Rubii Kondo; Yoshiaki Suzuki; Hisao Yamamura (Elsevier, 2023)
Pulmonary arterial hypertension (PAH) is a progressive and fatal disease that is characterized by vascular remodeling of the pulmonary artery. PAH remodeling is primarily caused by the excessive proliferation of pulmonary arterial smooth muscle cells (PASMCs). Therefore, an inhibitory mechanism is expected as a target for the treatment of PAH. Corosolic acid (CRA) is a pentacyclic triterpenoid extracted from the leaves of Banaba (Lagerstroemia speciosa) that exerts anti-diabetic, anti-inflammatory, and anti-tumor effects. In the present study, the effects of CRA on PAH remodeling were examined using PASMCs from idiopathic pulmonary arterial hypertension (IPAH) patients and monocrotaline (MCT)-induced pulmonary hypertensive (PH) rats. CRA inhibited the excessive proliferation of IPAH-PASMCs in a concentration-dependent manner (IC50 = 14.1 μM). It also reduced the migration of IPAH-PASMCs. The CRA treatment downregulated the expression of signal transducer and activator of transcription 3 (STAT3) in IPAH-PASMCs. In MCT-PH rats, the administration of CRA (1 mg/kg/day) attenuated increases in right ventricular systolic pressure, pulmonary vascular remodeling, and right ventricular hypertrophy. CRA also decreased the expression of STAT3 in pulmonary arterial smooth muscles from MCT-PH rats. In conclusion, the anti-proliferative and anti-migratory effects of CRA in PASMCs ameliorated PAH remodeling by downregulating STAT3 signaling pathways.